Tourist spending along the Way of Saint James. The Nós Way as an alternative pilgrimage route to Santiago - Araújo Vila, Noelia; Fraiz Brea, José Antonio; Rodríguez-Toubes Muñiz, Diego (Revista Galega de Economía, 2021)
Thanks to its different routes, the Way of Saint James continues to be one of the main tourist attractions in Galicia. Whether for religious or other reasons, every year a large number of pilgrims continue to arrive in Santiago de Compostela, providing great tourist opportunities for the municipalities that are located along the Way. This study analyses the current motivations that lead tourists to undertake the Saint James Way and the weight of their spending patterns during this experience. The insight of the “Nós” Way is assessed, a different route to Santiago from the traditional ones, as a new reality of the Way that can provide greater knowledge of the Galician territory. Quantitative research was chosen using a survey of 198 participants. The results show that the main motivation for following the Way is leisure, and that the age variable divides consumers into three distinct groups. Furthermore, despite the current global pandemic situation, a significant percentage of the sample completed the Way in 2020 (17.3%).